Pengaruh tata kelola perusahaan pada kinerja keuangan selama masa pandemi covid-19: Studi kasus pada perusahaan manufaktur sektor makanan dan minuman yang terdaftar di Bursa Efek Indonesia - Rizkyana, Fitrarena Widhi; Jannah, Richatul; Budiantoro, Risanda Alirastra; Meliana, Rini (Nur Science Institute, 2023)
The Covid-19 pandemic that hit almost the entire world, including Indonesia, poses a threat to economic growth, which has a multiplier effect on the company's financial condition. So this study aims to determine the impact of corporate governance on company financial performance during the Covid-19 pandemic in Indonesia. This study examines the relationship between the board of directors, the board of commissioners, the audit committee, and the company's financial performance. This research was conducted in 2020-2021 during the Covid-19 pandemic, and the research sample consisted of 26 companies that were selected purposively. The study results show that the size of the board of directors and independent commissioners significantly influences the company's financial performance. However, gender diversity of the board of directors, the qualifications of the board of directors, board of directors meetings and audit committee meetings do not significantly affect the company's financial performance. The novelty of this research is to consider secondary data in exploring corporate governance's effect on manufacturing companies' financial performance during the Covid-19 pandemic.